2020
DOI: 10.1093/sleep/zsaa221
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and high-risk behavior in military service members: a mega-analysis of four diverse U.S. Army units

Abstract: Experimental sleep restriction and deprivation lead to risky decision-making. Further, in naturalistic settings, short sleep duration and poor sleep quality have been linked to real-world high-risk behaviors (HRB), such as reckless driving or substance use. Military populations, in general, tend to sleep less and have poorer sleep quality than non-military populations due to a number of occupational, cultural, and psychosocial factors (e.g., continuous operations, stress, trauma). Consequently, it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Olson et al (2016) reported acute reductions in sleep duration, relative to an individual's typical duration, did not increase risk taking on the Iowa Gambling Task, but reduced sleep did shorten the time horizon over which information was integrated into participants' decisions. In a large sample (n > 2000) of active duty military personnel, Mantua et al (2021) reported that shorter habitual sleep duration was associated with an increased number of self-reported high risk behaviours. While total sleep time has been shown to influence cognition generally, and decision making specifically (Dickinson et al, 2016), sleep efficiency has not been well examined in the context of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Olson et al (2016) reported acute reductions in sleep duration, relative to an individual's typical duration, did not increase risk taking on the Iowa Gambling Task, but reduced sleep did shorten the time horizon over which information was integrated into participants' decisions. In a large sample (n > 2000) of active duty military personnel, Mantua et al (2021) reported that shorter habitual sleep duration was associated with an increased number of self-reported high risk behaviours. While total sleep time has been shown to influence cognition generally, and decision making specifically (Dickinson et al, 2016), sleep efficiency has not been well examined in the context of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were found compared to normal values, and negative mood states were found to have significant negative relationships with several domains of neurocognitive performance, while measures of positive mood states and sleepiness did not. Furthermore, recent data have shown that poor sleep quality slightly increased the risk of committing military-specific high-risk behaviors in four diverse U.S. Army samples of 2296 people aged approximately 25 years, and that a longer duration reduced the risk to a greater extent, even when controlling for a number of relevant demographic factors [25]. Longer sleep duration also predicted decreased high-risk behaviors.…”
Section: Sleep Schedules Quantity and Qualitymentioning
confidence: 96%
“…Cognitive functions such as working memory, complex attention, and problem solving deteriorate ( May and Kline, 1987 ; Libedinsky et al, 2013 ), leading to an increase in attentional lapses, performance errors, and injuries ( May and Kline, 1987 ; Nelson et al, 1995 ; Wright et al, 2012 ). Response inhibition is diminished ( Drummond et al, 2006 ), decision-making becomes inflexible ( Wimmer et al, 1992 ; Harrison and Horne, 1999 ; Maddox et al, 2009 ; Slama et al, 2018 ), and impaired risk management manifests in risky, net-loss decision-making ( Killgore et al, 2006 ; McKenna et al, 2007 ; Venkatraman et al, 2007 ; Pace-Schott et al, 2012 ; Womack et al, 2013 ; Mantua et al, 2021 ). Behavioral inhibition, which is maximized during the circadian day ( May and Hasher, 1998 ), declines as wakefulness proceeds into the circadian night ( Hasler et al, 2021 ).…”
Section: Nocturnal Changes In the Brainmentioning
confidence: 99%
“…Cognitive deficits associated with sleep inertia are exacerbated by chronic short sleep and abrupt awakenings during the circadian night ( Horne and Moseley, 2011 ; McHill et al, 2019 ), suggesting that both sleep loss and circadian factors contribute to nocturnal deficits in executive function. Of note, some of these studies were performed in military, physician, or other participants who were highly skilled and motivated for the task ( May and Kline, 1987 ; Nelson et al, 1995 ; Harrison and Horne, 1999 ; Maddox et al, 2009 ; Horne and Moseley, 2011 ; Mantua et al, 2021 ). Unfortunately, in all these studies, assessment was done during the day, not during the night of sleep deprivation.…”
Section: Nocturnal Changes In the Brainmentioning
confidence: 99%